HYPNOPARENTING; SEBUAH METODE MENJINAKKAN ALLIGATOR’S BRAINS PADA ANAK USIA DINI - Risa Alfiyah Ulfa (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2019)
every child must bring up the alligator's brain as a form of impinging psychological discomfort. Alligator's brain is a negative action taken by a child. The child's attitude is a reflection of what is done by the people closest to him, including the family which is the smallest community in children's education. Families play an important role in the realization of children who have good characteristics. Children who make negative actions are most likely because the closest environment is doing negative things, and vice versa. It takes a method that is able to minimize and even eliminate alligator's brain that is often raised by children when their psychological condition is uncomfortable. Hypnoparenting is a method that is able to tame alligator's brain. Hypnoparenting is an attempt by parents to bring children to the subconscious with the aim of influencing the child's mindset with which children can do good or bad. Hypnoparenting brings children from beta brain waves through alpha to tetha. When it reaches the wave of tetha, the child is able to accept positive suggestions from parents as an effort to tame the alligator's brain in children. Hypnoparenting provides maximum results if done continuously every day.